(untitled) (Journal of the College of Basic Education, 2022)
Lyrical works in the Iraqi theatrical text to enrich the dramatic act within the system of internal relations through its formation and interactions with other elements, leading to the manifestation of the aesthetics of lyricism through the production of the dramatic act in the structure of the events of the text and its collisions through the emotional statement and the act of revelation affecting the recipient, so it is important The research is to remove the ambiguity of the lyrical presence in the Iraqi theatrical text and to understand the enrichment mechanism between lyricism and the other elements that make up the text and shed light on the aesthetics of that fusion in the production of the dramatic act, and to introduce it by adopting one of the national experiences, as a model subject to analysis and study, to get to know those close to it. Interaction, marking the lyrical component as an important and influential positive presence